Blood Donor Networking and Its Follow up to Assure Sufficient Blood in Remote Border Area, Buntharik District, UbonRatchathani Province, Thailand - สุตาวงษ์, กรีพล (Journal of Health Science of Thailand, 2021)
Insufficient blood in remote border community hospitals is still the main concern for Thailand. It is very essential to have enough blood supply to serve the patients continuously. Blood from annual quota could be served for only a short period of time, therefore the new strategies to enhance blood donation were very important. The purposes for this research were to explore a mean to assure sufficient blood for Buntharik Hospital, Ubonratchathani Province through establishing blood donor networking, and to follow up the network for strong and sustainable blood donor group. In this study, some strategies were used to enhance blood donations such as the formation of a volunteer group among community leaders to recruit blood donors; using proactive methods for blood donor recruitment among the young people; and following up the recent donors by calling and messaging them. These strategies had resulted in the total blood units of 56.25% of the total blood supplies in the hospital, or the amount of 197 blood donations. The rest of those were walk-in blood donors. The research showed that these techniques could enhance blood donors more than half the used blood and assuring enough blood supply and avoiding zero blood situation. The used processes could reduce the cost of disbursement as well. If every hospital promoted blood donors by the red cross unit, together with strong blood donor networking and a good follow up, insufficient blood would be reduced or would not occur. There would be sufficient and sustainable blood supply for the hospital.